STRUCTURE IDENTIFICATION OF NON-LINEAR SYSTEM “MOVING OBJECT AND SERVO DRIVE” UNDER STOCHASTIC DISTURBANCES - Azarskov, Valerii; Blokhin, Leonid; Ermolaeva, Olga (Proceedings of National Aviation University (archive), 2016)
The article represents an algorithm for dynamics models identification of nonlinear system “moving object and servo drive”, taking into account that the stochastic disturbances presented in the real operating mode are acting on it.